Aberrant Glycosylation in Pancreatic Ductal Adenocarcinoma 3D Organoids Is Mediated by KRAS Mutations - Nakahashi, Hiromitsu; Oda, Tatsuya; Shimomura, Osamu; Akashi, Yoshimasa; Takahashi, Kazuhiro; Miyazaki, Yoshihiro; Furuta, Tomoaki; Kuroda, Yukihito; Louphrasitthiphol, Pakavarin; Mathis, Bryan J.; Tateno, Hiroaki (Journal of oncology, 2024)
Aberrant glycosylation in tumor cells is a hallmark during carcinogenesis. KRAS gene mutations are the most well-known oncogenic abnormalities but their association with glycan alterations in pancreatic ductal adenocarcinoma (PDAC) is largely unknown. We employed patient-derived 3D organoids to culture pure live PDAC cells, excluding contamination by fibroblasts and immune cells, to gasp the comprehensive cancer cell surface glycan expression profile using lectin microarray and transcriptomic analyses. Surgical specimens from 24 PDAC patients were digested and embedded into a 3D culture system. Surface-bound glycans of 3D organoids were analyzed by high-density, 96-lectin microarrays. KRAS mutation status and expression of various glycosyltransferases were analyzed by RNA-seq. We successfully established 16 3D organoids: 14 PDAC, 1 intraductal papillary mucinous neoplasm (IPMN), and 1 normal pancreatic duct. KRAS was mutated in 13 (7 G12V, 5 G12D, 1 Q61L) and wild in 3 organoids (1 normal duct, 1 IPMN, 1 PDAC). Lectin reactivity of AAL (Aleuria aurantia) and AOL (Aspergillus oryzae) with binding activity to α1-3 fucose was higher in organoids with KRAS mutants than those with KRAS wild-type. FUT6 (α1-3fucosyltransferase 6) and FUT3 (α1-3/4 fucosyltransferase 3) expression was also higher in KRAS mutants than wild-type. Meanwhile, mannose-binding lectin (rRSL [Ralstonia solanacearum] and rBC2LA [Burkholderia cenocepacia]) signals were higher while those of galactose-binding lectins (rGal3C and rCGL2) were lower in the KRAS mutants. We demonstrated here that PDAC 3D-cultured organoids with KRAS mutations were dominantly covered in increased fucosylated glycans, pointing towards novel treatment targets and/or tumor markers.